Nemlineáris, dinamikus rendszerek hatékony optimalizálásának egy lehetősége - Pletl, Szilveszter (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Evolution as a process has remarkable problem-solving abilities. Today the available technical items enable the successful use of genetic algorithms as a sort of model of evolu-tion is various fields of science. The procedure presented in this work combines the advan-tages of well-known soft techniques. Let it be assumed that the criterion function to be minimized has a global minimum. Let [!Beilleszthetetlen képlet, nézze meg a tanulmány szövegében!] be a criterion function. The aim is to determine the [!Beilleszthetetlen képlet, nézze meg a tanulmány szövegében!] global minimum. The use of the genetic algorithm in the stochastic-based search will most likely result in finding this minimum. In the further part of this work 9 will dente the free parameters of the system. The algorithms presented in this paper can be made parallel to a great extent and thus can be largely im-plemented in grid systems